Electricity Monitoring System based on Fuzzy Logic and Internet of things - Dawe, Alfonsius Yohandrik Bi (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
a smart home concept that has a remote control system based on the Internet of things, to provide convenience and security for owners to control household electronic equipment such as lights, tv, and fans, not only controlling the house but homeowners can monitor power, voltage, current and electricity bills in real-time as well as the status of the electrical load used in a lit state or not. And users can also limit the use of power to prevent overloads that impact rising bills or electricity usage costs—monitoring lighting automatically on the house's terrace using the fuzzy logic method and monitoring bathroom lights by detecting the presence and absence of movement. The switch system on electrical devices can be replaced using the ESP8266 microcontroller to be connected to android with the Openhabian application installed. This control system can also be done anywhere without area restrictions as long as the user can connect to the Internet.